Anxiety in adulthood: Strategic Cognitive Behavioral Treatment in a 24 years old female patient - Cavero Reap, Rocio del Pilar (2023)
The objective of the present study was to reduce anxious behaviors, promoting a repertoire of functional behaviors; in addition, to establish coping strategies to reduce anxiety symptoms, through the use of cognitive restructuring and relaxation techniques. According to its methodology, it was an experimental, single case study. The instruments used were: Interview and observation, the Millon III Multiaxial Clinical Inventory (Millon III), the State-Trait Anxiety Inventory (STAI) and the Zung Anxiety Self-Assessment Scale (Zung Test - EAA). Likewise, a multiaxial diagnosis, topographic and functional analysis was performed. Finally, a treatment plan was elaborated under a Cognitive-Behavioral approach and techniques such as programming of leisure and recreational activities, self-recording of behaviors, relaxation and breathing techniques, cognitive restructuring and psychoeducation were used. Finally, a favorable evolution of the patient was identified, through the integral evaluation, diagnosis and application of psychological techniques.